E-Commerce and Web Technologies 13th International Conference, EC-Web 2012, Vienna, Austria, September 4-5, 2012, Proceedings - Huemer, Christian; Lops, Pasquale (Lecture Notes in Business Information Processing, 2012)
This book constitutes the refereed proceedings of the 13th International Conference on Electronic Commerce and Web Technologies (EC-Web) held in Vienna, Austria, in September 2012. The 15 full and four short papers accepted for EC-Web, selected from 45 submissions, were carefully reviewed based on their originality, quality, relevance, and presentation. They are organized into topical sections on recommender systems, security and trust, mining and semantic services, negotiation, and agents and business services.